Goliath - Westerfeld, Scott (Westerfeld, Scott. Leviathan trilogy., 2011)
Alek and Deryn encounter obstacles on the last leg of their round-the-world quest to end World War I, reclaim Alek's throne as prince of Austria, and finally fall in love.